Terapi Hipnoquran Sebagai Upaya Mengurangi Trauma Perceraian Seorang Single Parent Di Desa Wonokerto Kecamatan Tekung Kabupaten Lumajang - Cholil, Cholil (Jurnal Bimbingan dan Konseling Islam, 2020)
The purpose of this research is to find out the process and outcome of hypnotic therapy in treating the trauma of a single parent. This study uses a qualitative descriptive approach, while the type of research used is case studies. Data collector techniques in the form of observations and interviews. The analysis used in this study is framing analysis done by emphasizing certain parts, highlighting certain aspects. Here the media selection, linking and highlighting events so that the meaning of the event is easier to touch and remember by the audience. As for the steps or procedure of Hipnoquran as follows: (1) Pre-Induction Talk; (2) induction; (3) deepening; (4) suggestion; (5) Termination. The final results after the implementation of hypnotic therapy are conducted among others: (1) The client has already spit a sense of sadness, disappointment, anger, and heartache during the therapeutic process, only these symptoms will reappear if the client is faced with events relating to the event of traumatic; (2) Currently the client is able to open a heart for a man who wants to be his life companion. The client’s negative perspective on men has changed after therapy; (3) Heart pounding and breathlessness no more when administering the third therapy